PENGEMBANGAN NILAI MULTIKULTURAL DALAM KURIKULUM 2013 - Supiyanto MA (Zawiyah: Jurnal Pemikiran Islam, 2015)
Curriculum 2013 has clearly adopted the integrated approach-monotheism seek to buildharmony and rationality transcendental region within the national education based on thereality of diversity and pluralism. Learners are expected to be the pioneers of creating andopening the way education necessitates tolerance, openness, and integration of knowledge.Competence of learners are willing to accept, appreciate, and run their religion is theanswer to the reality of the diversity of ethnic, cultural and religious. The presence of sixcharacters who reflect the diversity and ethnic groups in Indonesia, ranging from figuresderived from the ethnic Chinese to figures from Papua. The characters are present intextbooks namely Siti (girls veiled) and Lina (slanted eyes of ethnic Chinese) is a fact ofvalue and message of multicultural education in the curriculum of 2013. On the other hand,multicultural attitude manifests in the form of mutual respect, mutual help, mutual empathytoward others is clearly illustrated in the picture / visual has always been accompanyingcourse material.Keywords: Value Multicultural, Curriculum 2013